Premature rupture of membranes at term: factors associated to abdominal delivery - Muñoz Aznarán, Gisella (2015)
Objectives: To determine factors associated with abdominal delivery in pregnant women at term with prelabor rupture of membranes (PROM). Design: Descriptive retrospective case-control study. Setting: Hospital Nacional Cayetano Heredia, Lima, Peru. Participants: Pregnant women at term with PROM. Interventions: Study done in 140 women with prelabour rupture of membranes at 37 or more weeks’ gestation with no specific maternal or fetal contraindications to labor induction; 70 were control and 70 cases. Data were obtained from medical records. Main outcome measures: Factors associated to abdominal delivery. Results: Univariate analysis found uterine cervix status and preeclampsia as significant cesarean section risk factors. The final multivariable model analysis found maternal age, Bishop score less than 4, and preeclampsia as risk factors. The number of previous births was found as a protective factor. Conclusions: Cervical status (Bishop score less than 4), preeclampsia and maternal age were cesarean section risk factors in prelabor rupture of membranes. Multiparity was a protective factor.